The State of Alaska's early experience with institutionalization of health impact assessment - Anderson, Paul J. (Co-Action Publishing, 2013)
BACKGROUND: Many nations routinely include health impact assessments (HIA) in public policy decisions. Institutionalization of HIA formally integrates health considerations into a governmental decision-making process. We describe an example of institutionalization in the United States through Alaska's early experience with institutionalization of HIA. LITERATURE REVIEW: HIA arose from a series of health conferences in the 1970s that affirmed the importance of “health for all.” A number of key milestones eventually defined HIA as a unique field of impact assessment. There are several approaches to institutionalization, and one common approach in the United States is through the National Environmental Policy Act (NEPA). NEPA formed the basis for the earliest HIAs in Alaska. PROGRAM DESCRIPTION: Early HIAs in Alaska led to conferences, working groups, a state guidance document and the institutionalization of a HIA program within the Department of Health and Social Services in 2010. A medical epidemiologist staffs the program, which utilizes contractors to meet rising demand for HIA. The HIA program has sustainable funding from the state budget and from the state's natural resource permitting process. The HIA document is the main deliverable, but the program performs other tasks, including fieldwork and technical reviews. The HIA program works closely with a host of collaborative partners. CONCLUSION: Alaska's institutionalized HIA program benefits from sustainable funding that promotes continuous quality improvement and involves the program in the entire life cycle of a development project. The program structure adapts well to variations in workflow and supports a host of quality control activities. Currently, the program focuses on HIAs for natural resource development projects.